THE WAGE ANALYSIS OF CHART FLOATING FISHERMAN THE MOORING AT PELABUHAN PERIKANAN SAMUDERA BUNGUS WEST SUMATERA PROVINCE (CASE OF KM. PUTRI TUNGGAL 02 AND KM. PUTRI TUNGGAL 03) - Wiga Yullia Utami; Eni Yulinda; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research on the wage analysis of chart floating fisherman the mooring atPelabuhan Perikanan Samudera (PPS) Bungus West Sumatera Province, was conducted onJanuary 2015. This research purpose is to know how big is the ship owner wage and2JOM : Vol. 27 JUNI 2015fisherman workers of wage of KM. Putri Tunggal 02 and KM. Putri Tunggal 03, the wagepattern of this fisherman and the suitability of wage in the place with the act of the systemfor fisheries no. 16 1964. The method used in research was case study with respondentswere selected through non-probability sampling with accidental technic.The result of this research showed that the wage of the ship owner based wage for21 GT ship was 50% (Rp. 24.181.917) and for fisherman workers 50%, fishing master was18,18% (Rp. 5.216.636), chef abd mecanic was 13,64% (Rp. 3.912.477) and fishermancrew was 9,09% (Rp. 2.608.318). For fisherman owner of 30 GT ship was 50% (Rp.28.339.777) and for fisherman workers 50%, fishing master was 13,34% (Rp. 4.516.600),chef and mecanic was 10% (Rp. 3.387.450) and fisherman crew was 6,7% (Rp.2.258.300). The wage pattern in the place is familys system/habit. The wage in the placemore been extended then act of the system for fisheries no. 16 1964.Keyword: Analysis, Wage, Fisherman, Floating Ship and Pelabuhan Perikanan.